Hubungan Posisi Duduk Terhadap Kejadian Nyeri Punggung Bawah (Low Back Pain) Pada Penjahit Di Kelurahan Solor Kota Kupang Tahun 2017 - Ikun, Elisabeth Sri Intan; Nurina, Rr. Listyawati; Kareri, Dyah Gita Rambu (Cendana Medical Journal, 2023)
Background: Low back pain is a complaint that can reduce the productivity of human labor. Low back pain is rarely fatal but the perceived pain can make the patient experience a decrease in the ability to perform daily activities, occupational health problems, and many lost working hours in the age of productive and old age. One of the low back pain risk factors is work factors include workload, length of work and work attitude. Purpose: To analyze the Correlation of sitting position to low back pain occurrence at Tailor in KelurahanSolorKupang City 2017 Method: This research is an observational analytical research with cross sectional design conducted on tailor in Kelurahan Solor Kupang City by filling questioner and direct interview. The sampling technique used total sampling with 34 respondents who fulfilled inclusion and exclusion criteria. Data were analyzed using chi square test. Result: From this research, the result of 34 respondents who did the correct sitting position were 13 people (38.2%) of them were respondents with positive LBP as many as 4 people (11.8%) and negative LBP as many as 9 people (26.5%). Respondents who did the wrong sitting position were 21 people (61.8%) of whom were respondents with positive LBP as many as 16 people (47.1%) and negative LBP as many as 5 people (14.7%). The result of statistical test using chi-square test, obtained p value = 0.009 (p <0.05) Conclusion: There is a significant correlation between seated position to low back pain occurrence at tailor in Kelurahan Solor Kupang City 2017 with p value = 0.009 (p <0.05)